Safety of Digitalization of Educational and Social Space: Liudmila Baeva, Alexandr Grigorev (PJDOL, 2023)
The digitalization of education can radically change the essence of education as a space of communication, dialogue, socialization, forming not only knowledge but social skills as well. The goal of the study is to characterize and systematize social and anthropological risks of digitalization of educational institutions. The study is based on existential-axiological approach which concerns principles of safety communicative-educational environment as a phenomenon of e-culture.